Pengembangan Soal Matematika Model AKM Menggunakan Konteks Budaya Yogyakarta untuk Mengetahui Profil Literasi Matematika Siswa Sekolah Menengah Atas - Ahmad Heri Purwanto; Jailani Jailani (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
The purpose of this study was to develop AKM model mathematics questions using the Yogyakarta cultural context to determine the profile of mathematical literacy of high school students. This type of research is a design research type of development study using an emphasis on repeated cycle development using formative evaluation. This study developed a set of AKM model mathematics questions, with preliminary and prototyping stages. The subjects of the study were class X students of MAN 2 Wonosobo and were determined by partner teachers. Data analysis techniques used document analysis, walk through analysis, and test result analysis. The results of the study showed that: 1) a set of AKM model mathematics questions using the Yogyakarta cultural context that were compiled had met the valid criteria using the Formative Evaluation flow. 2) the results of the study of the profile of mathematical literacy of students in the field test subjects revealed that there were many students who had not completed, especially in the employ category where only 15% (6 out of 40 students) had completed it, namely on question number 8. Likewise in the formulate and interprete categories, both of which were no more than 17.5% of students who managed to get the maximum score. Likewise, in the content category, it can be seen that no more than 15% (6 out of 40 students) were able to obtain the maximum score on question number 8. Meanwhile, in the algebra domain, at least 32.5% (13 out of 40 students) managed to obtain the maximum score, namely on questions 23, 24 and 25. The same thing in the data domain can be seen to be higher than the number domain and geometry domain, although the percentage is quite low, namely 27.5% (11 out of 40 students) who obtained the maximum score.